Parental transfer of microcystin-LR induced transgenerational effects of developmental neurotoxicity in zebrafish offspring. (December 2017) - Wu, Qin; Yan, Wei; Cheng, Houcheng; Liu, Chunsheng; Hung, Tien-Chieh; Guo, Xiaochun; Li, Guangyu
Abstract: Microcystin-LR (MCLR) has been reported to cause developmental neurotoxicity in zebrafish, but there are few studies on the mechanisms of MCLR-induced transgenerational effects of developmental neurotoxicity. In this study, zebrafish were exposed to 0, 1, 5, and 25 μg/L MCLR for 60 days. The F1 zebrafish embryos from the above-mentioned parents were collected and incubated in clean water for 120 h for hatching. After examining the parental zebrafish and F1 embryos, MCLR was detected in the gonad of adults and F1 embryos, indicating MCLR could potentially be transferred from parents to offspring. The larvae also showed a serious hypoactivity. The contents of dopamine, dihydroxyphenylacetic acid (DOPAC), serotonin, gamma-aminobutyric acid (GABA) and acetylcholine (ACh) were further detected, but only the first three neurotransmitters showed significant reduction in the 5 and 25 μg/L MCLR parental exposure groups. In addition, the acetylcholinesterase (AChE) activity was remarkably decreased in MCLR parental exposure groups, while the expression levels of manf, bdnf, ache, htr1ab, htr1b, htr2a, htr1aa, htr5a, DAT, TH1 and TH2 genes coincided with the decreased content of neurotransmitters (dopamine, DOPAC and serotonin) and the activity of AChE. Neuronal development related genes, α1-tubulin, syn2a, mbp, gfap, elavl3, shha and gap43 were also measured, but gap43 was the gene only up-regulated. Our results demonstrated MCLR could be transferred to offspring, and subsequently induce developmental neurotoxicity in F1 zebrafish larvae by disturbing the neurotransmitter systems and neuronal development. Graphical abstract: Highlights: MCLR could be transferred from parents to offspring and induce developmental neurotoxicity in F1 zebrafish larvae. Parental transfer of MCLR interfered with neurotransmitter systems of F1 zebrafish larvae. The disruption of the neuronal development might contribute to the change of neurobehavior in F1 zebrafish larvae. Abstract : MCLR could be transferred from parental zebrafish to offspring and cause transgenerational neurotoxic developmental effects by affecting the neuronal development and neurotransmitter systems such as dopamine signaling system, serotonin system, and cholinergic system.